2020
DOI: 10.3390/cells9030534
|View full text |Cite
|
Sign up to set email alerts
|

Functions of Vertebrate Ferlins

Abstract: Ferlins are multiple-C2-domain proteins involved in Ca2+-triggered membrane dynamics within the secretory, endocytic and lysosomal pathways. In bony vertebrates there are six ferlin genes encoding, in humans, dysferlin, otoferlin, myoferlin, Fer1L5 and 6 and the long noncoding RNA Fer1L4. Mutations in DYSF (dysferlin) can cause a range of muscle diseases with various clinical manifestations collectively known as dysferlinopathies, including limb-girdle muscular dystrophy type 2B (LGMD2B) and Miyoshi myopathy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 230 publications
(408 reference statements)
2
38
0
1
Order By: Relevance
“…A C2 domain contains 100–130 amino acids and can mediate interaction with membranes by binding Ca 2+ and negatively charged lipids such as phosphatidylserine (PS) or phosphatidylinositol 4,5-bisphosphate (PIP2). In a recent study of Otoferlin C2 domains, the binding of Ca 2+ was indicated for all C2 domains with the exception of C2A [ 49 , 50 ] ( Figure 2(a) ). The C2C and C2F domains of Otoferlin preferentially bind PIP2, and PIP2 may target Otoferlin to the presynapse in a calcium-independent manner [ 51 ].…”
Section: Mechanisms Of Ribbon Synapse Damagementioning
confidence: 95%
“…A C2 domain contains 100–130 amino acids and can mediate interaction with membranes by binding Ca 2+ and negatively charged lipids such as phosphatidylserine (PS) or phosphatidylinositol 4,5-bisphosphate (PIP2). In a recent study of Otoferlin C2 domains, the binding of Ca 2+ was indicated for all C2 domains with the exception of C2A [ 49 , 50 ] ( Figure 2(a) ). The C2C and C2F domains of Otoferlin preferentially bind PIP2, and PIP2 may target Otoferlin to the presynapse in a calcium-independent manner [ 51 ].…”
Section: Mechanisms Of Ribbon Synapse Damagementioning
confidence: 95%
“…Dysferlin and otoferlin have been the most studied. Dysferlin is critical for muscle development and functions in vesicular trafficking and lysosome exocytosis during muscle plasma membrane damage repair [ 38 , 87 ]. Dysferlin does not localize to lysosomes in intact myotubes, but dysferlin-containing vesicles fuse with lysosomes upon sarcolemma damage, possibly in response to a raise in [Ca 2+ ] c [ 88 ].…”
Section: Resultsmentioning
confidence: 99%
“…Either way, dual roles in membrane fusion and vesicle trafficking are also seen in the vertebrate ferlins [ 86 ], such as otoferlin in replenishment of synaptic vesicles [ 40 , 41 ] through myosin VI [ 114 , 115 ]. The role of dysferlin in vesicular trafficking in quite diverse [ 38 ], but is also dependent on actin myosin for plasma membrane repair [ 116 ]. Overall, these observations and similarities with vertebrate ferlins indicate that the role of FER1 changes under different conditions organellar trafficking during intracellular replication, and microneme exocytosis upon activation of egress, during gliding and host cell invasion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to its multiple C2 domains, myoferlin participates in the tethering of vesicles to membranes and to the calcium sensing. An extensive and excellent review has been recently published on the functions of ferlins in vertebrates [22]. Myoferlin expression is increased in a large panel of cancer cells and tumors, where most of the studies described its role in the recycling of membrane receptors (EGFR, IGFR, .…”
Section: Discussionmentioning
confidence: 99%